The role of good governance on institutional quality as a FDI motivator in the Malaysian case - Narayanan, Sridevi R.K. (2014)
Malaysia, as well as other developing countries has been the recipients of FDI and (foreign direct investments) over the past few decades.These investments have proven to be a source of economic growth for the host countries.However, in recent years, there seem to be a strong competition among developing countries to attract FDI as the importance of FDI in developing the host country through increased employment and resource usage hence GDP growth cannot be overlooked.This article examines the role of institutional fitness in FDI considerations.The World Governance Indicator (WGI) which includes voice and accountability, political stability, absence of violence, government effectiveness, regulatory quality, rule of law and control of corruption as the main issues of governance.We will examine these indicators for Malaysia over a period of 1996-2012 and predict the path for Malaysia as a FDI destination for the coming years.If indeed these indicators are of importance, for FDI consideration as proclaimed in FDI literature, then is Malaysia having the advantage compare to its neighbors like Singapore, Indonesia and Thailand? In order to ensure these indicators are encouraging signals, good governance is a necessary condition